Pro-Inflammatory Response of Bovine Polymorphonuclear Cells Induced by Mycoplasma mycoides subsp. mycoides - Di Federico, Marta; Ancora, Massimo; Luciani, Mirella; Krasteva, Ivanka; Sacchini, Flavio; Orsini, Gianluca; Di Febo, Tiziana; Di Lollo, Valeria; Mattioli, Mauro; Scacchia, Massimo; Marruchella, Giuseppe; Cammà, Cesare (Frontiers in Veterinary Science, 2020)
Mycoplasma mycoides subsp. mycoides (Mmm) is the etiological agent of contagious bovine pleuropneumonia (CBPP), one of the major diseases affecting cattle in sub-Saharan Africa. Some evidences suggest that the immune system of the host (cattle) plays an important role in the pathogenic mechanism of CBPP, but the factors involved in the process remain largely unknown. The present study aimed to investigate the cell response of bovine polymorphonuclear neutrophils (PMNs) after Mmm in vitro exposure using one step RT-qPCR and Western blotting. Data obtained indicate that gene and protein expression levels of some pro-inflammatory factors already change upon 30 minutes of PMNs exposure to Mmm. Of note, mRNA expression level in Mmm exposed PMNs increased in a time-dependent manner and for all time points investigated; targets expression was also detected by western blotting in Mmm exposed PMNs only. These data demonstrate that when bovine PMN cells are triggered by Mmm, they undergo molecular changes, upregulating mRNA and protein expression of specific pro-inflammatory factors. These results provide additional information on host-pathogen interaction during CBPP infection.